Peer Monitoring vs. search costs in the interbank market: Evidence from payment flow data in Norway - Jon H. Findreng (Norges Bank, 2021)
Bilateral payment flows between banks may provide private information about a borrowing bank's liquidity position. This paper analyses whether private information on the bilateral payment flow of central bank reserves foster peer monitoring or whether the information is used to reduce search costs in the unsecured interbank market. In the former, banks with outflows of liquidity are penalized by their counterparties, while in the latter, these banks benefit through reduced search costs to find a liquidity provider. I use data from Norges Bank's real time gross settlement system over the period 2012 to 2015 to identify unsecured overnight interbank loans and payment flows. The results suggest that banks are using private information from payment flows to reduce search costs and not for peer monitoring. This has important implications for regulators' assessment of the pros and cons of a centralized versus a decentralized interbank market.
hdl:11250/2758395
Keywords: G21; E42; E43; E58; 330; Peer monitoring; search cost; unsecured overnight interbank market; interest rates; central bank liquidity policy and OTC markets